Experimental investigation of the effect of long-term water exposure on dielectric materials - Eugenia L. Stanisauskis Weiss; Emily L. Guzas (Polymer Testing)
Recent work studying dielectric materials has produced increases in dielectric permittivity and dielectric loss in dielectric elastomer materials, leading to increased material performance. However, little is known about the aging and breakdown of these materials within a marine environment, which could affect material performance. A basic study of the aging and breakdown of two different state-of-the-art dielectric materials, 3M's Very High Bond (VHB) 4910 and bi-axially oriented polypropylene (BOPP), in a marine environment is completed. To begin, accelerated life tests are conducted to obtain artificially aged samples, aged to a maximum duration of 12 months in distilled water. Cyclic and non-cyclic tensile loading testing are used to characterize the material fatigue of the unaged vs aged samples and to determine how the material properties change over time when exposed to a simulated marine environment. For VHB, aging seems to transition the hyperelastic (non-linear) behavior to purely elastic (linear) behavior. As aging level and stretch rate increase, the point of maximum elongation decreases and elastic modulus increases. Similar observations are noted for BOPP, although the effect of its bi-axial orientation must be considered. An increase in stretch rate causes an increase in elastic modulus, and the effect of aging looks to be dependent on orientation where for the orientation normal to the long axis, the elastic modulus increases as aging increases and for the orientation parallel to the long axes, the elastic modulus decreases as aging increases. For BOPP, orientation plays a greater effect on stress and elastic modulus than aging or stretch rate.